Hadis-hadis ‘Azl (Kb) Studi Takhrij Hadis - Fadilla Febriani; Nur Aisah Simamora (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to trace, collect, and analyze hadiths about azl (traditional contraception) using the takhrij hadith approach in order to obtain normative validity for the practice of birth control in Islam. Although azl is a practice known since the time of the Prophet Muhammad ﷺ and was carried out by his companions, its legal discourse still leaves debate in the treasury of fiqh. In the modern context, the issue of contraception is part of the discourse on reproductive health and family ethics that urgently needs to be reviewed based on authentic primary Islamic sources. The method used in this study is qualitative-descriptive based on literature studies with the takhrij hadith approach. The takhrij steps include identifying hadith texts through digital devices, tracking hadith sources in Kutub at-Tis‘ah and musnad books, sanad criticism using classical jarḥ wa ta‘dīl references, matan analysis, and determining the degree of hadith based on the science of muṣṭalaḥ al-ḥadīth. The results of the study found four main lines of hadith about azl originating from the companions of Jabir bin ‘Abdillah, Abu Sa‘id al-Khudri, ‘Abdullāh bin Mas‘ūd, and atsar ‘Umar bin al-Khaṭṭāb. The first two narrations have the degree of ṣaḥīḥ li-dzātihi, one narration is ḥasan li-ghayrihi, and one has the status of ḍa‘īf. These findings indicate that the majority of hadith about azl have strong validity and there is not a single explicit prohibition from the Prophet against the practice. Thus, azl can be understood as a contraceptive practice that is permitted in Islam, as long as it is carried out by agreement and does not aim to eliminate offspring absolutely. This study contributes to strengthening the foundation of hadith in the discourse of contraception fiqh and opens up opportunities for integration between hadith studies, maqāṣid al-syarī‘ah, and the ethical needs of contemporary Muslim families.